Contract Farming Models and Their Implementation on Broiler Chicken Business Income in Nanga-Nanga District, Kendari City - Abdul Gafaruddin; La Ode Arfan Dedu Arfan (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The Nanga-Nanga subdistrict in Kendari City is one of the subdistricts whose community has developed a broiler chicken farming business in partnership with a company, but the implementation of the partnership sometimes does not comply with the contract.Purpose: of this study is to examine the contractual partnership model (contract farming) applied in broiler production in the Nanga-Nanga District of Kendari City, to evaluate the effectiveness of its implementation, and to analyze how the overall execution of the contractual partnership influences the income earned by broiler farmers.Design/methodology/approach: his research design employs a descriptive and quantitative approach, utilizing correlation analysis to examine relationships between variables. The study sample comprised the entire population of broiler chicken farmers involved in a partnership scheme with the company, totaling 15 respondents. Both primary and secondary data were collected for analysis. Correlation analysis was applied to evaluate the data. In addition, the study assessed several critical components of broiler chicken businesses, including income, mortality rate, average body weight, feed conversion ratio (FCR), performance index, and depreciation cost calculations.Findings/Result: The contractual partnership arrangement (contract farming) implemented in the Nanga-Nanga District of Kendari City is characterized as a bipartite model. With respect to feed provision, 40% of farmers reported that the company supplied feed in quantities that surpassed the actual requirements of their poultry, while 20% stated that the feed they received was insufficient for their livestock. In terms of operational activities, particularly the timeliness of input delivery, only 46.67% of farmers confirmed that deliveries were made according to the agreed schedule. Furthermore, compliance with the company-determined harvest and sales schedules especially regarding harvest timing reached 60%. On average, farmers recorded a total income of IDR5,786,368.80. Results from Spearman’s Rank Correlation analysis show a strong positive association between the implementation of contractual partnerships and broiler farm income, reflected in a correlation coefficient of 0.771.Conclusion: The contractual arrangement used in broiler production in the Nanga-Nanga District of Kendari City corresponds to a two-party cooperation structure. The implementation of the partnership was evaluated across three dimensions, showing different levels of execution: support related to production inputs demonstrated an exceptionally strong degree of fulfillment, operational activities were carried out at a moderately effective level, and harvest timing and sales management also showed a moderate level of implementation. Overall, the way the contract farming scheme is executed demonstrates a strong positive relationship with the income earned by broiler chicken farmers.Originality/value (State of the art): The primary contribution of this study lies in its dual focus: not only does it identify the types of contract models, but it also evaluates the degree to which these contracts are implemented. The implementation process was examined across three distinct dimensions: the supply of essential production inputs, the management of day-to-day operational processes, as well as the timing of harvesting and sales. Keywords: broilers; partnership model; implementation of partnership pattern, chicken farming business, contract farming